Mapping agency comparing regionalisms in Africa - Lorenz-Carl, Ulrike (International political economy of new regionalisms series, 2013)
Mapping Agency provides an empirically rich 'African perspective' on regionalisms in Sub-Saharan Africa. It adopts an actor-centred approach but departs from a rather simplified understanding of agency as exerting power and instead scrutinizes to what extent actors actually participate in or are excluded from processes of regionalism